A preliminary study on debt perception towards Malaysian University student - Masnih Mustapa; Musaiyadah Ahmadun; Muzalifah Monil; Nur Ilma Ambo (Global Academic Excellent, 2024)
Debt has become an increasingly worrying issue among students of higher education institutions in Malaysia. A pilot study was conducted using survey techniques to assess the level of financial knowledge, attitudes, and practices among 33 students from faculty accounting at Universiti Teknologi Mara Kota Kinabalu Branch, Sabah. The research instrument consisted of structured questionnaires. The pilot study findings indicate a significant gap between respondents' knowledge, attitudes, and financial practices. Therefore, a fullscale study is proposed to investigate the perception of debt among students at this university in greater depth. The findings from this study are hoped to assist the university and government in formulating appropriate awareness and intervention programs to address student debt issues.